Pulse and switching circuits - Ketchum, Donald J. (McGraw-Hill, 1965)
The material is presented here in a manner to provide a common denominator of circuits which may lead toward radar, television, test equipment, instrumentation, and/or computers. Complete system analysis of each of these areas is beyond the scope of this book.